Retrieval of an IVCF retained for over 6 years via femoral venous approach using a large-bore sheath: a case report and literature review - Yuan, Gang; Hu, Wei; Wang, Weiming; Xu, Yanneng; Cui, Ran; Zhang, Xun; Luo, Jianming; Si, Guangyan (Frontiers in Cardiovascular Medicine, 2025)
Prolonged retention of inferior vena cava filters (IVCF) predisposes patients to complications, including caval thrombosis, filter tilt, wall adherence, fibrotic adhesion, migration, and perforation, posing significant risks to patient health. Retrieval of long-term retained filters is challenging, as standard retrieval techniques often prove ineffective. Advanced strategies are therefore required to improve success rates. Herein, we report a case of an IVCF retained for over 6 years, in which the patient developed acute thrombosis of the inferior vena cava (IVC) and iliac veins following recent discontinuation of anticoagulation. Concurrently, the retrieval hook was embedded in fibrotic tissue with wall apposition, and the filter struts had perforated the vascular wall with dense adhesions. Initial attempts using a standard retrieval kit failed. Subsequently, a loop snare technique was employed to dissect perihook fibrotic tissue, successfully engaging the retrieval hook. However, due to the filter's firm incorporation into the IVC, the hook straightened under traction, resulting in retrieval failure. Ultimately, the stubborn filter was successfully removed via a retrograde approach using a 20F vascular sheath through the femoral vein. By detailing this case and reviewing relevant literature, we aim to provide insights into advanced retrieval strategies for challenging IVCF, particularly those with prolonged dwell times.